Exiting a Lawless State - Hoff, Karla; Stiglitz, Joseph E. (2012)
An earlier paper showed that an economy could be trapped in an equilibrium state in which the absence of the rule of law led to asset-stripping and the prevalence of asset-stripping led to the absence of a demand for the rule of law, highlighting a coordination failure. This article looks more carefully at the dynamics of transition from a non-rule-of-law state. The article identifies a commitment problem as the critical feature inhibiting the transition: the inability, under a rule of law, to forgive theft. This can lead to the perpetuation of the non-rule-of-law state, even when it might seem that the alternative is Pareto-improving.